Stress, coping and presenteeism in nurses assisting critical and potentially critical patients - Juliane Umann; Laura de Azevedo Guido; Rodrigo Marques da Silva (SciELO, 2014)
Objective to verify the associations between stress, Coping and Presenteeism in nurses operating on direct assistance to critical and potentially critical patients. Method this is a descriptive, cross-sectional and quantitative study, conducted between March and April 2010 with 129 hospital nurses. The Inventory of stress in nurses, Occupational and Coping Questionnaire Range of Limitations at Work were used. For the analysis, the Kolmogorov-Smirnov test, correlation coefficient of Pearson and Spearman, Chi-square and T-test were applied. Results it was observed that 66.7% of the nurses showed low stress, 87.6% use control strategies for coping stress and 4.84% had decrease in productivity. Direct and meaningful relationships between stress and lost productivity were found. Conclusion stress interferes with the daily life of nurses and impacts on productivity. Although the inability to test associations, the control strategy can minimize the stress, which consequently contributes to better productivity of nurses in the care of critical patients and potentially critical.